UJI AKTIVITAS TABIR SURYA DAN ANTIOKSIDAN EKSTRAK ETANOL DAUN SUNGKAI (Perenema canescens Jack) - Fadlilaturrahmah Fadlilaturrahmah; Amalia Khairunnisa; Aditya MP Putra; Ivanna Sinta (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Indonesia, which is located in the tropics, causes people's skin to easily experience premature aging and tan. Most of these cosmetic products contain dangerous synthetic chemicals. For this reason, cosmetic products with natural active ingredients or phytocosmetics that are effective and safe to use need to be developed. One of the typical natural plant plants from South Kalimantan that has the potential to be developed as a cosmetic preparation is Sungkai (Peronema canescens Jack). The aim of the study was to determine the antioxidant activity and sunscreen activity of Sungkai leaves. The method used for the determination of antioxidant activity is the DPPH method using a uv-vis spectrophotometer and for the determination of sunscreen activity using a uv-vis spectrophotometer. The results showed that the P. canescens plant extract contained anthraquinones, flavonoids, saponins, tannins, and phenols. P.canescens plants have an Inhibitory Concentration 50 (IC50 ) of 42.219±19.440 ppm and have sunscreen activity with spf (Sun Protecting Factor) values ??with concentrations of 600 ppm, 400 ppm, 200 respectively as follows: 24±0.31; 16±0.34; and 8±0.3. The conclusion of this study Sungkai (Peronema canescens Jack) has antioxidant activity and has sunscreen activity so that it has the potential to be developed into natural skin care.